Relationship between personality traits and physical activity levels among university students at UNIKL MICET / Kamalia Nadhirah Zainal Ariffin - Zainal Ariffin, Kamalia Nadhirah (2018)
The aim of this study was to examine the relationship between personality traits and physical activity levels among university students at Unjkl Micet. The data was collected by using questionnaires. The sample of this study consisted of 402 students of University Kuala Lumpur Malaysian Institute of Chemical and Bioengineering Technology (Unikl Micet). Personality trait was assessed by using the International Personality Item Pool (IP[P; Goldberg, 1999) and physical activity level was assessed by using the International Physical Activity Questio1maire (lPAQ). All the data were analyzed by using the Statistical Package for the Social Sciences (SPSS) software version 23. There are 2 statistical analyses which are descriptive statistics and inferential statistics. Descriptive statistics was used for assessing the percentages, mean, mode and standard deviation and inferential statistics, Pearson Con-elation Coefficient was used to identify whether there is any relationship between personality traits and physical activity. As a result, Unikl Micet's student has conscientiousness personality and moderate physical activity level. Lastly, there is no relationship between personality traits and physical activity levels among university students at Unikl Micet. In conclusion, by recognize the personality of students still cannot determine their level of physical activity.